2012
DOI: 10.1089/gtmb.2012.0148
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleotide Polymorphism at CYP27B1-1260, but Not VDR Taq I, Is Possibly Associated with Persistent Hepatitis B Virus Infection

Abstract: Background: Vitamin D, beyond its role in calcium and bone metabolism, exhibits immunomodulatory effects on innate and adaptive immune pathways and is suggestively related to liver diseases. Objective: This study investigated the association of single-nucleotide polymorphisms in genes involved in vitamin D functions with hepatitis B virus (HBV) infection. Methods: Five hundred Chinese Han subjects, including 274 chronic HBV patients, 68 HBV infection resolvers, and 158 healthy controls without HBV infection, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…9 studies were eligible to be included in the meta-analysis (Alagarasu et al, 2012;Bellamy et al, 1999;Cohen, 2004;Janssen et al, 2007;Kresfelder et al, 2011;de la Torre et al, 2008;D. E. Roth et al, 2008;Suneetha et al, 2006;Zhu et al, 2012). Characteristics of the studies fitting the inclusion criteria are reported in Table 1 and FokI and TaqI and were genotyped in 6 of the selected studies.…”
Section: Selection Process and Study Characteristicsmentioning
confidence: 99%
“…9 studies were eligible to be included in the meta-analysis (Alagarasu et al, 2012;Bellamy et al, 1999;Cohen, 2004;Janssen et al, 2007;Kresfelder et al, 2011;de la Torre et al, 2008;D. E. Roth et al, 2008;Suneetha et al, 2006;Zhu et al, 2012). Characteristics of the studies fitting the inclusion criteria are reported in Table 1 and FokI and TaqI and were genotyped in 6 of the selected studies.…”
Section: Selection Process and Study Characteristicsmentioning
confidence: 99%
“…Moreover, common single nucleotide polymorphisms (SNPs) in vitamin-D-related genes, including vitamin D receptor (VDR), vitamin D binding protein (DBP) and enzymes that initiate vitamin D formation such as 1-a-hydroxylase (encoded by CYP27B1), are shown to be associated with clinical outcome and response to PEG-IFN-based therapy in patients with chronic HCV infection [5][6][7][8][9]. Among HBV-infected individuals, recent studies have suggested a possible role of these SNPs in viral persistence and HCC development [10,11]. In addition, it has recently been demonstrated that a variant of CYP27B1 is associated with high probability of response to PEG-IFN therapy in an Italian cohort of HBeAg-negative CHB [12].…”
Section: Association Of Vitamin-d-related Genetic Variations and Treamentioning
confidence: 99%
“…The polymorphisms within the vitamin D receptor (VDR) and 1‐ α ‐hydroxylase (CYP27B1) were recently associated with virological response to PEG‐IFN and ribavirin in HCV treatment , with onset of oral cancer , type 1 diabetes and autoimmunity disorders ; moreover, a possible role in the natural course of HBV infection was recently reported by Zhu et al . , but no data were available about the treatment with PEG‐IFN in HBV.…”
Section: Introductionmentioning
confidence: 99%